A review of the taxonomic position of Vesbius seyrigi Villiers, 1970, with a description of two new species of Peyrierocoris Chłond & Junkiert, 2010 (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) - Chłond, Dominik (Zootaxa, 2014)
Peyrierocoris seyrigi (Villiers, 1970) is redescribed and its taxonomic position is revised to accommodate Vesbius seyrigi Villiers, 1970, erroneously described under the generic name Vesbius Stål, 1865. Redescription and drawings of the dorsal habitus and characters of the male and female genitalia, as well as a drawing of the ovarian egg of P. seyrigi (Villiers, 1970), are given. Two new species, P. gorczycai sp. nov. and P. herczeki sp. nov., are described and illustrated with 21 figures.